CONDITIONS AND FORMS OF MARRIAGE IN MORDVIN CUSTOMARY LAW - Sushkova, Iuiia (Revista Inclusiones, 2020)
The significance of this study derives from the increasing need to explore popular legal traditions as well as socio-economic, ethnic, cultural and religious aspects of the life of peoples in the context of legal pluralism. In common law, special attention is given to matrimonial law, which reproduces and affects, at a specific micro-level, almost every aspect of traditional jurisprudence. In this regard, the research aims to reveal conditions and forms of marriage in Mordvin customary law. The major research methods adopted in this study are field ethnography and case studies used to conduct an in-depth investigation of customary rules in different areas of their application. The study analyses customary specificities related to spouse selection, highlights matchmaking as the main form of marriage and, finally, examines practices such as abduction and samokrut. The results of the research can be used to strengthen the institutions of marriage and family in present-day Russia.